Relevansi Pemaknaan Hijrah pada QS: An-Nisa’ (4): 100: Studi atas Mufassir Abad Modern - Azis Fatkhurrohman, Abdul (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Hijrah as one of the phenomena recorded in the history of Islam during the time of the Prophet Muhammad Saw, is again associated by a number of Islamic preachers on social media. The conversation was prompted by the recent